2005
DOI: 10.1242/jeb.01710
|View full text |Cite
|
Sign up to set email alerts
|

Effects of series elasticity and activation conditions on muscle power output and efficiency

Abstract: The activation of a muscle depends on the function that it is performing and on the architectural properties of that muscle; the two are inextricably linked. Activation conditions such as activation timing, duration and amplitude can be varied throughout a cyclical movement (such as locomotion) and the length change of the whole muscle tendon unit (MTU) can also be varied. Architecturally, muscles have a range of fibre lengths, maximum force-producing capabilities and stiffness of the series elastic element (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
64
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 22 publications
7
64
0
Order By: Relevance
“…2003) and changed tendon mechanical properties (Karamanidis and Arampatzis. 2005;Kubo et al 2003;Morse et al 2005) favor different kinds of muscle activation for optimal efficiency and power output in these two age groups (Lichtwark and Wilson. 2005b).…”
Section: Discussionmentioning
confidence: 99%
“…2003) and changed tendon mechanical properties (Karamanidis and Arampatzis. 2005;Kubo et al 2003;Morse et al 2005) favor different kinds of muscle activation for optimal efficiency and power output in these two age groups (Lichtwark and Wilson. 2005b).…”
Section: Discussionmentioning
confidence: 99%
“…Translated to gibbon tendons, this would mean that the gibbon Achilles tendon, with a relative compliance (i.e. RC=1/S×MVC/FL) of 10%, would achieve a muscle efficiency of ~32%, while the patellar tendon, with an RC of 3%, would have an efficiency of ~26% [by comparison, the RC of 'stiff' rat Achilles tendon is 5%, while the 'compliant' wallaby Achilles tendon has a RC of 35% (Litchwark and Barclay, 2010;Lichtwark and Wilson, 2005a)]. Compliant tendons are particularly important to improve the power output of short-fibred muscles, which have a restricted shortening range, such as the triceps surae in gibbons and humans.…”
Section: Discussion Gibbon Achilles and Patellar Tendon: Elastic Enermentioning
confidence: 99%
“…In addition, it has been shown that tendons also have an important role in reducing the cost of locomotion by: (1) reducing the amount and rate of shortening of muscle fibres, allowing near-isometric force production and contraction in their optimal fibre length range (Biewener and Roberts, 2000;Lichtwark and Wilson, 2005a;Lichtwark and Barclay, 2010); and (2) acting as elastic springs, storing and releasing elastic strain energy during locomotion (Alexander, 1984;Alexander, 2002). Such an energy-saving function has been demonstrated for different tendons in a wide range of species, such as the hind limb tendons in hopping kangaroos and wallabies (Dawson and Taylor, 1973;Alexander and Vernon, 1975;Biewener and Baudinette, 1995;Ker et al, 2000) and the Achilles tendon in humans (Lichtwark and Wilson, 2005b;.…”
Section: Introduction Tendons As Elastic Energy Storesmentioning
confidence: 99%
“…It appears that increasing relative shortening duration above 50% offsets the potentially efficiency-reducing effect of increasing stimulation duty factor (Table2) (Curtin and Woledge, 1996;Lichtwark and Wilson, 2005). This is not surprising as the detrimental effect of increasing stimulus duty factor is thought to be due to the continuation of energy turnover into lengthening (Curtin and Woledge, 1996).…”
Section: Initial Mechanical Efficiency and Length Trajectorymentioning
confidence: 99%